Book Review: A Brief History of South Africa: From Earliest Times to the Mandela Presidency - Mandla J. Radebe (The Thinker)
The writing of South African history has been contentious, mainly due to the exclusion of the majority African people whose past achievements have often been ignored or treated contemptuously. Various tendencies in the writing of this history sought to dispute Africans’ claim to South Africa. The Afrikaner tendency, for example, portrayed Africans as not being indigenous to this country (Theal, 1897). On the other hand, the liberal tradition considered South Africa as constituting a single nation with white people making up the core while black people in general, and Africans in particular, had to be integrated on the basis of meeting particular standards (Nxumalo, 1992).